Switch on, switch off - Berger, Melvin; Croll, Carolyn (New York : Crowell, 1989)
Explains how electricity is produced and transmitted, how to create electricity using an electrical wire and a magnet, how generators supply electricity for cities, and how electricity works in homes.
Elem. School Library Collection
Elem. School Library Collection.
School Library Journal
School Library Journal.
Wilson's Children
Wilson's Children.
Keywords: Electricity -- Juvenile literature; Electricity; Electricity